(untitled) (SAARC Journal of Agriculture, 2025)
Soil types have a huge influence on germination and the emergence of plant and tree seeds. Soil is formed through weathering of the parent rock material. This normally happens when the rocks are exposed to agents of erosion such as wind and rain. The quality of any soil is critical for seed germination to be successful. This is because of its influences on air circulation, water retention and nutrient absorption rate and availability. There are chemical, physical and biological soil quality indicators. This article was a review of different soil types and their impact on germination and emergence of plant seeds. Dark clays form from the crystallization of minerals from molten materials under high temperatures and pressure. Climate, slope and relief also influence soil formation. The physical properties of soil such as texture, structure, depth, consistency, color, permeability and porosity were identified as having influence on the germination and emergence of plant seeds in different soil types. Organic matter rich clay soils had a 75 percent germination of the African giant sunflower. While soil type had an influence on germination of the Amaranth plant, it is crusting that strongly reduces germination. Helianthus annus L had lower seed germination due to poor aeration and water logging. Plant species such as Acacia sieberana had best germination in sand soil and lower in clays while Cola nitridated could be propagated in any soil type. SAARC J. Agric., 23(1): 184-195 (2025)